Archetypal Criticism: The Notion Of Monomania Overturns The Hero's Journey - Ahmad Muhyiddin B Yusof; Nooraileen Ibrahim; Nur Azmina Binti Mohamad Zamani; Mohd Muzhafar Idrus (Universiti Kebangsaan Malaysia, 2024)
Indexed by MyCite